Keywords of Identity, Race, and Human Mobility in Early Modern England - Das, Nandini (Amsterdam University Press, 2021)
What did it mean to be a stranger in sixteenth and seventeenth-century England? How were other nations, cultures, and religions perceived? What happened when individuals moved between languages, countries, religions, and spaces? Following the model of Raymond Williams's classic Keywords: A Vocabulary of Culture and Society (1976), Keywords of Identity, Race, and Human Mobility analyses a selection of terms that were central to the conceptualisation of identity, race, migration, and transculturality in the early modern period. In many cases, the concepts, preconceptions, and debates that they embody - or sometimes subsume - came to play formative roles in the articulation of identity, rights, and power in subsequent periods. Together, the essays in this volume provide an invaluable resource for anyone interested in the development of issues of identity, belonging, and human mobility.